2008
DOI: 10.1002/syn.20580
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent differences in dopamine transporter and vesicular monoamine transporter‐2 function and their implications for methamphetamine neurotoxicity

Abstract: The abuse of methamphetamine (METH) is a serious public health problem because METH can cause persistent dopaminergic deficits in the brains of both animal models and humans. Surprisingly, adolescent postnatal day (PND)40 rats are resistant to these METH-induced deficits, whereas young adult PND90 rats are not. Studies described in this report used rotating disk electrode voltammetry and western blotting techniques to investigate whether there are age-dependent differences in monoamine transporter function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…For DAT, D2R and GABA VT, it was possible to establish a statistically significant relationship, particularly in the group of children under 6 months of age from whom most of our sample was drawn. Age-related changes in DAT functionally active protein have been described in rats (Volz et al 2009), showing a decrease between young adolescent rat levels and adult levels. Interestingly, in the same report, no difference between VMAT 2 immunoreactivity in the two groups was found, although conflicting data had previously been published (Volz et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For DAT, D2R and GABA VT, it was possible to establish a statistically significant relationship, particularly in the group of children under 6 months of age from whom most of our sample was drawn. Age-related changes in DAT functionally active protein have been described in rats (Volz et al 2009), showing a decrease between young adolescent rat levels and adult levels. Interestingly, in the same report, no difference between VMAT 2 immunoreactivity in the two groups was found, although conflicting data had previously been published (Volz et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of dopaminergic transmission, the vesicular monoamine transporter-2 (VMAT2) is responsible for the loading of dopamine (DA) and other monoamines into synaptic vesicles (Cartier et al 2010). The DA transporter (DAT) carries DA across the plasmalemmal membrane from the synaptic cleft into the cytoplasm (Volz et al 2009). The central actions of DA are mediated by five distinct receptors that belong to the G-protein receptor family.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the extensive changes occurring in the brain during adolescence (Andersen et al 1997(Andersen et al , 2000Dagher et al 2001;Koss et al 2014;Juraska and Willing 2017), another possibility is that differences in pharmacodynamics (e.g. dopamine transporter function; Volz et al, 2009) contribute to our findings. Further studies will be required to determine the impact of pharmacokinetics and pharmacodynamics on age-and sex-differences in drug seeking.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies in rat striatal membranes showed that the B max of [ 3 H]GBR-12935 binding peaked at 2 months [19] or 3 months of age [20] and declined substantially in the subsequent 9 months. Furthermore, the uptake rate of [ 3 H]dopamine in rat striatal synaptosomes, which is mediated by DAT, decreased between 1 and 3 months [21]. Similarly, striatal DAT protein concentrations decreased in post-mortem human material between preadolescents and young adults [22].…”
Section: Discussionmentioning
confidence: 96%